Penggunaan AB MIX dan ZPT Hormonik terhadap Pertumbuhan serta Hasil Tanaman Kailan (Brassica oleracea L.) secara Hidroponik NFT - Simanullang, Sejahtera; Ernita, Ernita (Jurnal Agroteknologi, Agribisnis, dan Akuakultur, 2026)
This study aims to determine the interaction of AB-Mix and Hormonic PGR (plant growth regulator) on the growth and yield of kailan (Brassica oleracea L.) hydroponically NFT. The research was carried out in the greenhouse of the Faculty of Agriculture, Islamic University of Riau, Jalan Kaharudin Nasution No. 113, Air Cold Village, Bukit Raya District, Pekanbaru City. This research was conducted for 1 month from November to December 2022. This research used a Factorial Split Plot Design which consisted of two factors. The first factor is AB Mix (A) as the main plot which consists of 4 levels, namely 1000 ppm, 1250 ppm, 1500 ppm, 1750 ppm. The second factor was Hormonic PGR (Z) as a subplot consisting of 4 levels, namely 0, 2, 4, 6 cc/L Water. Parameters observed were plant height, number of leaves, plant economic wet weight, plant dry weight, and root volume. The experimental data were analyzed for variance and continued with a follow-up test for Honest Significant Differences (HSD) at the 5% level. The results showed that the interaction between AB Mix and Hormonic PGR had a significant effect on plant height, number of leaves, plant dry weight, and root volume. The best treatment is the combination of AB Mix 1750 ppm and Hormonic PGR 4 cc/L water. The main effect of real AB Mix on all parameters with the best treatment is 1750 ppm. The main effect of real hormonal PGR on all parameters with the best treatment is 4 cc/L of water.